Alteration and Reorganization of Functional Networks: A New Perspective in Brain Injury Study - Castellanos, Nazareth P.; Bajo, Ricardo; Cuesta, Pablo; Villacorta-Atienza, José A.; Paúl, Nuria; Garcia-Prieto, Juan; Del-Pozo, Francisco; Maestú, Fernando (Frontiers in Human Neuroscience, 2011)
Plasticity is the mechanism underlying brain’s potential capability to compensate injury. Recently several studies have shown that functional connections among brain areas are severely altered by brain injury and plasticity leading to a reorganization of the networks. This new approach studies the impact of brain injury by means of alteration of functional interactions. The concept of functional connectivity refers to the statistical interdependencies between physiological time series simultaneously recorded in various brain areas and it could be an essential tool for brain function studies, being its deviation from healthy reference an indicator for damage. In this article, we review studies investigating functional connectivity changes after brain injury and subsequent recovery, providing an accessible introduction to common mathematical methods to infer functional connectivity, exploring their capabilities, future perspectives and clinical uses in brain injury studies.